2012
DOI: 10.1037/a0027099
|View full text |Cite
|
Sign up to set email alerts
|

Hypermasculinity in the media: When men “walk into the fog” to avoid affective communication.

Abstract: Men's tendency to exhibit withdrawal behaviors during affective communication has been shown to be a point of contention in romantic discord. The current study was designed to examine whether men's desire to facilitate a discussion regarding affective communication would be affected by media portrayals of subtle versus blatant withdrawal; the latter epitomized by a hypermasculine man who opts to leave an emotionally tense situation, while it is evident that his distressed female partner desires communication. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The findings about gender are consistent with research indicating that men may experience gender role conflict and have negative attitudes related to help seeking and psychotherapy (Pedersen & Vogel, 2007). Women felt that it was culturally appropriate for them to be immediate, supporting research on gender stereotypes (Ben-Zeev, Scharnetzki, Chan, & Dennehy, 2012;Harrison & Shortall, 2011).…”
Section: Predictors Of Training Outcomesupporting
confidence: 80%
“…The findings about gender are consistent with research indicating that men may experience gender role conflict and have negative attitudes related to help seeking and psychotherapy (Pedersen & Vogel, 2007). Women felt that it was culturally appropriate for them to be immediate, supporting research on gender stereotypes (Ben-Zeev, Scharnetzki, Chan, & Dennehy, 2012;Harrison & Shortall, 2011).…”
Section: Predictors Of Training Outcomesupporting
confidence: 80%
“…Similarly, other studies have documented the effect of priming masculinities on numerous outcomes, such as men's decreased desire to engage in affective communication (Ben-Zeev et al, 2012), men's increased intention to commit sexual assault (Edwards & Vogel, 2015), men's decreased gender role conflict (Jones & Heesacker, 2012), and women's improved performance on mental rotation tasks (Ortner & Sieverding, 2008).…”
Section: Domain 3: Situational Masculinitiesmentioning
confidence: 93%
“…For example, men hearing male-related words from a car radio drove faster in a driving simulator compared to neutral or feminine conditions, presumably because of the activation of risk-taking masculine norms (Mast et al, 2008; see also Meier-Pesti & Penz, 2008, on masculinity primes and financial risk taking). Similarly, other studies have documented the effect of priming masculinities on numerous outcomes, such as men’s decreased desire to engage in affective communication (Ben-Zeev et al, 2012), men’s increased intention to commit sexual assault (Edwards & Vogel, 2015), men’s decreased gender role conflict (Jones & Heesacker, 2012), and women’s improved performance on mental rotation tasks (Ortner & Sieverding, 2008).…”
Section: Domain 3: Situational Masculinitiesmentioning
confidence: 94%
“…For men, mentors tend to be of the same sex, and they tend to encourage traditional gendered behavior and even hypermasculinity in terms of social relationships and emotions (Messner 1992;Scheff 2006;Welch 1997). Hypermasculinity "leads to competition rather than connection between persons" (Scheff 2006:3), and perhaps explains the different communication patterns described by the men and women in their interviews; as studies have shown, hypermasculinity diminishes men's ability to forge connections and communicate emotions (Ben-Zeev et al 2012). Within hypermasculine environments of high school sports, we see this reflected in the young men's confessions of not opening up to their mentors because they were not really-as one participant phrased it-"an emotional person," or have never been "one to be emotionally attached to people."…”
Section: Discussionmentioning
confidence: 99%
“…Hypermasculinity “leads to competition rather than connection between persons” (Scheff 2006:3), and perhaps explains the different communication patterns described by the men and women in their interviews; as studies have shown, hypermasculinity diminishes men’s ability to forge connections and communicate emotions (Ben‐Zeev et al. 2012). Within hypermasculine environments of high school sports, we see this reflected in the young men’s confessions of not opening up to their mentors because they were not really—as one participant phrased it—“an emotional person,” or have never been “one to be emotionally attached to people.” Despite this potentially problematic effect of masculinity, participants expressed that “learning to be a man” provided them with self‐esteem, work ethic, and heightened athletic ability.…”
Section: Discussionmentioning
confidence: 99%